Systemism - Claudius Gräbner-Radkowitsch; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2024)
This short paper discusses the concept of "systemism", elaborates how it implicitly underpinned most seminal works of evolutionary-institutional economics, and explains how future research would benefit from making the systemist nature of evolutionary economics more explicit. More precisely, the paper clarifies the ontological and epistemological claims associated with systemism, and describes how the explicit use of systemism can support a pluralist meta-paradigm in heterodox economics and political economy in general, and evolutionaryinstitutional economics research in particular.
Keywords: 330; Evolution; Institutions; Ontology; Epistemology; Models; Multi-Level Theorising; Emergence; Complexity